Legal Politics on Criminal Sanctions in The Article of Fraud 378 Revision of Criminal Code in The Revision of National Criminal Law - Hasib, Mohammad; Djatmika, Prija; Navianto, Ismail; Aprilianda , Nurini (Technium Social Sciences Journal, 2020)
Politics in criminal law is one part of a law development plan that is carefully designed with due Regard to the accompanying aspects that Pancasila as the basis of the state becomes a source of Substantive values including the number and sources of law. Criminal law is considered good if it meets and complies with the values community and to fulfill a sense of justice in the community in accordance with the times that one side overrides the principle of legality, but the other side also prioritizes living law. This is evident in the provisions of the criminal sanctions under Article 378 of the KUHP. This article aims to find out the Political Law of Criminal Sanctions Article 378 of the Criminal Code in Reforming the National Criminal Law. Sanctions that are deemed not fulfilling a sense of justice that is only a Maximum of 4 years imprisonment cause socio-biological, philosophical and juridical problems. The results of research on several provisions of Fraud (Bedrog) and fraudulent acts in national legislation as well as the opinions of experts can be concluded that the reformulation of the formulation of sanctions in Fraud (Article 378) in the Criminal Code Law in the future can be put in (Chapter XXV Concerning Fraud) by imposing new sanctions. Namely fines and heavier imprisonment if they meet the new elements that have been formulated.